2014
DOI: 10.1371/journal.pntd.0002601
|View full text |Cite
|
Sign up to set email alerts
|

Standardising Visual Control Devices for Tsetse Flies: Central and West African Species Glossina palpalis palpalis

Abstract: Background Glossina palpalis palpalis (G. p. palpalis) is one of the principal vectors of sleeping sickness and nagana in Africa with a geographical range stretching from Liberia in West Africa to Angola in Central Africa. It inhabits tropical rain forest but has also adapted to urban settlements. We set out to standardize a long-lasting, practical and cost-effective visually attractive device that would induce the strongest landing response by G. p. palpalis for future use as an insecticide-impregnated tool i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 31 publications
2
20
0
1
Order By: Relevance
“…In coordinated field trials in West Africa, we have already shown that 1 m 2 black and blue targets covered with adhesive film capture 4–5 times more G. tachinoides than biconical traps [22] . Electric net results from interpretative experiments elsewhere in Africa [22] , [26] imply that tsetse attraction to targets could be underestimated when adhesive film is used by up to 50% (for some riverine species). This may mean that targets are even better at attracting G. f. fuscipes and G. tachinoides to land than our East African data suggest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In coordinated field trials in West Africa, we have already shown that 1 m 2 black and blue targets covered with adhesive film capture 4–5 times more G. tachinoides than biconical traps [22] . Electric net results from interpretative experiments elsewhere in Africa [22] , [26] imply that tsetse attraction to targets could be underestimated when adhesive film is used by up to 50% (for some riverine species). This may mean that targets are even better at attracting G. f. fuscipes and G. tachinoides to land than our East African data suggest.…”
Section: Discussionmentioning
confidence: 99%
“…This is worth emphasising, as it is the landing response that underlies the principle of using insecticide-impregnated targets as control devices for tsetse. It is already well established for a range of tsetse species that only some of the flies attracted to the vicinity of traps or landing on their surfaces are eventually captured [18] , [23] , [26] . In the absence of a gold standard against which to assess the efficiency of electric nets and/or adhesive film in enumerating tsetse (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A tsetse repellant formulation mimicking the odor of waterbuck ( Kobus ellipsiprymnus defassa ), a non-host animal, was recently developed and used as an innovative collar device to protect cattle from tsetse bites and AAT [60]. Visual cues have been extensively exploited in the development of improved traps – stationery and mobile targets impregnated with insecticides for riverine/”palpalis” [6163] and savannah/”morsitans” [49,64] groups of tsetse. However, it has been noted that for the morsitans group of tsetse flies, including G. pallidipes and G. swynnertoni , host odors play a more significant role than visual cues as they strongly attract the tsetse flies across long ranges of up to 100 m [65].…”
Section: Discussionmentioning
confidence: 99%
“…Pengamatan dilakukan pada jam aktifnya lalat yaitu pada pukul 08.00 sampai 14.00 , setelah jam 14.00 perangkap pipet yang sudah dipasang diambil dan lakukan pengamatan serta penghitungan berapa jumlah lalat yang terperangkap pada stik perangkap lalat pada masing-masing warna. 8,21,[26][27][28] Penelitian ini dilakukan pengulangan sebanyak 6 kali pengulangan. 29 Data yang diperoleh dari observasi dikelompokan dalam bentuk tabel kemudian dianalisis secara deskriptif dan dilanjutkan dengan uji statistik.…”
Section: Bahan Dan Metodeunclassified